TREND AND CHARACTERISTICS OF THE EXTERNAL DEFICIT IN ROMANIA IN THE POST PANDEMIC PERIOD - Camelia MILEA (Financial Studies)
The external disequilibrium has been a constant of the Romanian economy since 1990, and it represents one of the main vulnerabilities of the national economy. In the article1, the author analyses the evolution of Romania's foreign deficit during the recent years, highlighting some of its characteristics. The research shows that the external deficit is generated by the negative balances of goods and of primary income, and it is partly offset by the surplus of the balances of secondary income and services. It is also shown that the structure of Romanian exports is dominated by goods with low added value and a low degree of processing, which do not help to obtain high prices in foreign markets. The economic slowdown of the European Union countries (the main trade partners of Romania) in recent years is a cause of the slower growth of Romanian exports. The methodology used joins the descriptive analysis with the empirical analysis and data interpretation, as well as the identification of correlations.